Biogenic synthesis and antibacterial activity of silver nanoparticles (AgNPs) produced by Phomopsis sp. strain GFPA2 - Sutjaritvorakul, Thanawat; Chutipaijit, Sutee (My University, 2018)
Silver nanoparticles (AgNPs) have many applications in different fields such as electronic industries, chemical industries, medical diagnostics and detergent products. In this research AgNPs were produced by Phomopsis sp. GFPA2 isolated from zinc mineral rocks, and were successfully synthesized by using fungal culture broth. The biogenic crystals were investigated and identified by field emission scanning electron microscopy (FE-SEM) equipped with energy dispersive X-ray spectroscopy (EDS) and X-ray powder diffraction (XRD). The spectra confirmed that the biogenic crystals were AgNPs, and they are mostly spherical in shape. The crystals were also tested for their antibacterial activity against human pathogenic bacteria such as Escherichia coli ATCC 27853, Pseudomonas aerogenosa ATCC 27853, Bacillus cereus ATCC 6633 and Staphylococcus aureus ATCC 25623. The result showed that the biogenic AgNPs can inhibit the growth of both Gram positive and Gram negative pathogenic bacteria. Therefore, these biogenic AgNPs could be used to treat the infection caused by human pathogenic bacteria.
Keywords: Antibacterial activity; Biosynthesis; Fungi; Silver nanoparticles (AgNPs)